2020
DOI: 10.3168/jds.2020-18350
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for test-day milk yield, lactation persistency, and fertility in low-, medium-, and high-production systems in Kenya

Abstract: Genetic parameters for test-day milk yield, lactation persistency, and age at first calving (as a fertility trait) were estimated for the first 4 lactations in multiplebreed dairy cows in low-, medium-, and high-production systems in Kenya. Data included 223,285 test-day milk yield records from 11,450 cows calving from 1990 to 2015 in 148 herds. A multivariate random regression model was used to estimate variance and covariance components. The fixed effects in the model included herd, year, and test month, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
4
4
0
Order By: Relevance
“…A very similar result was found for similar smallholder crossbred cattle in Kenya [8]. For purebred and crosses between Bos taurus dairy breeds in Kenya, Wahinya et al [19] also reported a lack of a typical lactation curve but it occurred at substantially higher production levels. This raises the question: to what extent is the response of the shape of the lactation curve to a lower input environment a function of the genotype of cow?…”
Section: Discussionsupporting
confidence: 71%
“…A very similar result was found for similar smallholder crossbred cattle in Kenya [8]. For purebred and crosses between Bos taurus dairy breeds in Kenya, Wahinya et al [19] also reported a lack of a typical lactation curve but it occurred at substantially higher production levels. This raises the question: to what extent is the response of the shape of the lactation curve to a lower input environment a function of the genotype of cow?…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, the trend and range of additive genetic variations of MY during lactation (Figure 1A) were consistent with those of Japanese Holstein cows (Togashi et al, 2008). Many studies have shown that the cows with high MY have greater genetic variances than low-yield cows (Togashi et al, 2008;Wahinya et al, 2020). These higher additive variances indicate that the cows are more genetically diverse (Wahinya et al, 2020).…”
Section: Discussionsupporting
confidence: 77%
“…The additive genetic variances, permanent environmental variances, and the heritabilities of five milkrelated traits changing during lactation were assessed in this study (Figure 1), which revealed that the genes or the expression of genes that control these milk-related traits might differ along the lactation trajectory of cows (Wahinya et al, 2020). The scope of the additive genetic variances of the MY in this study (Figure 1A) was higher than that in cows in North Carolina and Portugal (Silvestre et al, 2005), but was in the same range as the cows in medium-and high-production systems in Kenya (Wahinya et al, 2020). Furthermore, the trend and range of additive genetic variations of MY during lactation (Figure 1A) were consistent with those of Japanese Holstein cows (Togashi et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations